Correlation between Democratic Communication Style in Families and Pro-social Development in Preschool Children (Aged 4-5 Years) - Nur Laili Tri Supatmi; D Darsinah (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the relationship between family communication style and pro-social development in children aged 4-5 years. Methodology: This study employs a quantitative approach using a correlational research design. The population consisted of all children aged 4-5 years and their parents who were involved as research subjects. The sample comprised 74 children and 74 parents. Data were analyzed using simple linear regression to examine the effect of family communication style on children's pro-social development. Results: The results indicate a significant relationship between family communication style and pro-social development in children aged 4-5 years. The simple linear regression analysis produced a t-value of 2.056 with a significance level of 0.025, demonstrating that family communication style has a significant effect on children's pro-social development. The F-test yielded an F value of 4.336 with a significance of 0.000, confirming that the regression model was appropriate for analysis. Furthermore, the coefficient of determination (R²) was 0.782, indicating that family communication style contributed 78.2% to children's pro-social development, while the remaining variance was influenced by other factors beyond this study. Applications/Originality/Value: The findings highlight the important role of family communication style in fostering pro-social development among children aged 4-5 years. Better communication practices within the family are associated with higher levels of empathy, sharing behavior, and positive social interaction in children. This study provides valuable insights for parents, educators, and practitioners in early childhood education to enhance children's social development through effective family communication.